Spatial Frequency Tuning during the Conscious and Non-Conscious Perception of Emotional Facial Expressions – An Intracranial ERP Study - Willenbockel, Verena; Lepore, Franco; Nguyen, Dang K.; Bouthillier, Alain; Gosselin, Frédéric (Frontiers in Psychology, 2012)
Previous studies have shown that complex visual stimuli, such as emotional facial expressions, can influence brain activity independently of the observers’ awareness. Little is known yet, however, about the “informational correlates” of consciousness—i.e., which low-level information correlates with brain activation during conscious vs. non-conscious perception. Here, we investigated this question in the spatial frequency (SF) domain. We examined which SFs in disgusted and fearful facial expressions modulate activation in the insula and amygdala over time and as a function of awareness, using a combination of intracranial event-related potentials (ERPs), SF Bubbles (Willenbockel et al., 2010a), and Continuous Flash Suppression (CFS; Tsuchiya and Koch, 2005). Patients implanted with electrodes for epilepsy monitoring viewed face photographs (13° x 7°) that were randomly SF filtered trial-by-trial. In the conscious condition, the faces were visible; in the non-conscious condition, they were rendered invisible using CFS. Data were analyzed by performing multiple linear regressions on the SF filters from each trial and the transformed ERP amplitudes across time. The resulting classification images suggest that many SFs are involved in the conscious and non-conscious perception of emotional expressions, with those between 6 and 10 cycles per face width being particularly important early on. The results also revealed qualitative differences between the awareness conditions for both regions. Non-conscious processing relied on low SFs more and was faster than conscious processing. Overall, our findings are consistent with the idea that different pathways are employed for the processing of emotional stimuli under different degrees of awareness. The present study represents a first step to mapping with a high temporal resolution how SF information “flows” through the emotion-processing network and to shedding light on the informational correlates of consciousness in general.